Assessment of an Exchange Rate’s Fluctuations Impact on the Foreign Exchange Market - Solodzhuk, Tetiana; Myhovych, Tetiana (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The article analyzes the foreign exchange market functioning under the influence of exchange rate fluctuations. The main factors determining the exchange rate in the existing conditions have been determined. All course-forming factors are divided into fundamental ones, which include the main economic indicators; technical conjunctural; extraordinary (unexpected) and non-economical. The formation of the forward currency operations market trends, in particular forward contracts, currency swaps, options and other financial instruments, was also investigated. The income trends of the current currency market from quotes of the most used currency pairs are briefly described. It was concluded that the most predictable indicator in the current currency operations market is the standardized exchange rate, determined on the basis of currency quotes of at least 6 commercial banks. When calculating the average arithmetic rate, the highest and lowest quotation rates are not taken into account. The future foreign exchange market trends depend on the choice of the monetary policy vector, which is based on a qualitative and quantitative assessment. Since the processes in the currency market have a fractal structure and cannot be predicted using classical methods, the provisions of the fractal statistics theory are used for this purpose. In particular, on the basis of existing quotations of the currency pair US dollar/Ukrainian hryvnia, the Hurst indicator, which reflects the level of anti-persistence of the national currency exchange rate dynamics, was calculated, and accordingly, its ability to change trends to the opposite in periods of high volatility and in the presence of factors that cause it. The volatility of the national currency rate and the level of anti-persistence of currency fluctuations depends on a number of measures in the field of currency regulation and currency and monetary policy. At the same time, any intervention of the state government in the exchange rate formation process causes a change in the trend. The results of the calculations can be used for operational and strategic planning of the business entities behavior on currency markets and measures aimed at countering the negative impact of exchange rate changes.